How controlled drainage and peat subsidence affect the hydrology of cultivated peatlands under changing climatic conditions - Salla, Aleksi; Salo, Heidi; Tähtikarhu, Mika; Koivusalo, Harri (Elsevier, 2025)
Sustainable cultivation of peatlands is challenged by drainage induced acceleration of peat decomposition, which leads to substance fluxes and peat subsidence. Controlled drainage (CD) is designed to allow sufficient drainage for cultivation practices while excessive drainage can be avoided during other times. There is a remaining research gap in the potential of CD to affect field hydrology under changing climate. In this study, the functioning of CD in a peat covered field was simulated using a hydrological model driven by climate scenarios (RCP8.5 and RCP4.5) for two locations in Finland, southern Salo and northern Ruukki. Simulation of peat subsidence was included for the near future period of 2041–2060. Different climate scenarios resulted in varying hydrological impacts, especially during winter. During the historical period, CD decreased average groundwater table (GWT) depths by 0.10–0.13 m, the impact being similar in both locations. Average summer GWT depths were decreased by 0.06–0.09 m. CD reduced average drain discharge by 32–37 mm/a in Salo and by 14–19 mm/a in Ruukki. The performance of CD remained stable in the future climate scenarios. The simulated peat subsidence rates were 0.9–1.4 cm/a without CD, and CD reduced subsidence by 14–22 %. Subsidence decreased average GWT depths, CD effect on GWT depths, and drain discharge, but increased the CD effect on drain discharge. CD has relevance in reducing peat decomposition in Nordic peatland fields under current and future climate, but more effective reduction likely requires irrigation during growing season.
Keywords: peatland hydrology; agricultural hydrology; climate change; hydrological modeling; agricultural water management